Moisture-heat-resistant metallized film and preparation method thereof

By using a combined structure of a network-shaped nanocarbon porous layer and a modified oil layer in the capacitor film, the moisture erosion problem caused by the unstable oil layer morphology is solved, and higher moisture and heat resistance is achieved.

CN119820935AActive Publication Date: 2025-04-15TONGLING CHAOYUE ELECTRON CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510029657.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The oil layer of the existing moisture-resistant thermal capacitor film is unstable, resulting in the exposed part of the metal layer being easily eroded by moisture. A metallized film that can effectively prevent moisture erosion and its preparation method are needed.

Method used

A metallized film structure is adopted that includes a network-shaped nanocarbon porous layer and a modified oil layer. The modified oil layer is composed of silicone oil and additives, which include nanotitanium dioxide, modified nanosilica and polymethyl methacrylate. Through the combination and treatment of these components, a stable protective layer is formed.

Benefits of technology

Through the combination of the network-shaped nanocarbon porous layer and the modified oil layer, the agglomeration and transfer of the oil layer are effectively avoided, the integrity of the metal layer is ensured, and the moisture and heat resistance of the capacitor is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119820935A_ABST
    Figure CN119820935A_ABST
Patent Text Reader

Abstract

The invention discloses a damp-heat-resistant metallized film and a preparation method thereof. The damp-heat-resistant metallized film comprises an insulating dielectric layer, a metal layer and a protective layer, the protective layer comprises a network-shaped nano-carbon porous layer and a modified oil layer, the modified oil layer comprises the following components in parts by weight: 90-100 parts of silicone oil and 0.05-0.2 part of an additive, a microscopic'anchoring site 'is formed on the surface of the network-shaped nano-carbon porous layer, and when the modified oil layer is coated on the surface of the network-shaped nano-carbon porous layer, the surface of the modified oil layer is not damaged; silicone oil molecules and additives in the silicone oil molecules can be embedded into the sites, so that the network-shaped nano-carbon porous layer is firmly combined with the silicone oil molecules, an oil layer can be uniformly dispersed in the initial coating stage, large agglomeration is avoided, and the modified oil has a good oil-absorbing effect due to the fact that part of oil permeates into pores of the network-shaped nano-carbon porous layer. The movement range of the oil molecules is limited, so that the whole oil layer is restrained, and the problem of agglomeration or transfer is effectively avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metallized films, in particular to a moisture-heat resistant metallized film and a preparation method thereof. Background Art

[0002] Film capacitors are used in home appliances, electric vehicles and charging equipment to mitigate current shocks and filter alternating circuits. The principle is to store charge in two mutually insulated metal thin layers; the metal thin layer is arranged on the surface of the polymer film and is wound together with the polymer film to form a stacked structure of metal layers and polymer layers. Because each layer is very thin, the film capacitor can provide a large enough surface to store charge.

[0003] The oil-plated layer can be used to manufacture moisture- and heat-resistant capacitor films. The oil layer has a small amount of oil and low cost. It is a more common production method for moisture- and heat-resistant capacitor films today. The oil layer covers the surface of the metal layer. Because the oil layer is more hydrophobic than the metal, it can prevent water vapor from directly contacting the metal surface and prevent metal oxidation. However, since the oil layer is liquid and has the characteristics of agglomeration and transfer, the morphology of the oil layer on the surface of the metal layer is unstable, and the exposed part of the metal layer is easily corroded by moisture. Therefore, there is an urgent need for moisture- and heat-resistant metallized films and preparation methods thereof to solve this problem. Summary of the invention

[0004] The present invention aims at the deficiencies in the prior art and provides the following technical solutions:

[0005] A moisture and heat resistant metallized film, comprising an insulating dielectric layer, a metal layer and a protective layer;

[0006] The protective layer comprises a network-shaped nano-carbon porous layer and a modified oil layer, wherein the modified oil layer comprises the following components in parts by weight: 90-100 parts of silicone oil and 0.05-0.2 parts of additives.

[0007] As an improvement of the above technical solution, the additive includes nano titanium dioxide, modified nano silicon dioxide and polymethyl methacrylate, and the mass ratio of the nano titanium dioxide, modified nano silicon dioxide and polymethyl methacrylate is (1-1.5): (0.5-1): (1-2).

[0008] As an improvement of the above technical solution, the thickness of the insulating dielectric layer is 3 μm-8 μm, the thickness of the metal layer is 20 nm-40 nm, and the thickness of the protective layer is 10 nm-30 nm.

[0009] As an improvement of the above technical solution, the preparation method of the modified nano-silicon dioxide comprises the following steps: the modified nano-silicon dioxide is surface treated with a silane coupling agent to obtain the modified nano-silicon dioxide.

[0010] The method for preparing the moisture-heat resistant metallized film comprises the following steps:

[0011] S1: slowly adding terephthalic acid into a methanol solvent, stirring to dissolve it, forming a terephthalic acid solution with a concentration of 0.01-0.1 mol / L, adding zinc nitrate into another portion of methanol solvent, stirring to fully dissolve the zinc nitrate, and obtaining a 0.05-0.2 mol / L transparent zinc ion solution;

[0012] S2: 0.01-0.1 g / mL polyethylene glycol is added to the zinc ion solution and mixed evenly to form a mixed solution. The insulating dielectric layer with the metal layer is immersed in the mixed solution. The terephthalic acid solution is slowly added to the mixed solution. The temperature is 25-35 ° C. The reaction time is 1-3 hours. The zinc ions and terephthalic acid molecules will gradually diffuse to the surface of the metal layer to form a continuous MOF layer on the surface of the metal layer.

[0013] S3: transferring the metal film grown with MOF to a high-temperature furnace in an inert atmosphere for carbonization treatment to form a network-like nano-carbon porous layer;

[0014] S4: Evenly mix the silicone oil and the additive according to the ratio to form a modified oil, and spray the modified oil onto the network-shaped nano-carbon porous layer in batches until the required thickness of the protective layer is reached.

[0015] As an improvement of the above technical solution, in step S4, it is necessary to wait for 15-20 minutes after each spraying and perform drying at a temperature of 40-80°C.

[0016] As an improvement of the above technical solution, in step S3, the heating rate of the high temperature furnace is 1-5°C / min, and the carbonization temperature is 500°C-800°C.

[0017] Beneficial effects of the present invention:

[0018] Microscopic "anchoring sites" are formed on the surface of the network-like nano-carbon porous layer. When the modified oil layer is coated thereon, the silicone oil molecules and the additives therein can be embedded in these sites, so that the network-like nano-carbon porous layer is firmly combined with the silicone oil molecules, so that the oil layer can be evenly dispersed in the initial coating stage to avoid large agglomerations. Since part of the modified oil penetrates into the pores of the network-like nano-carbon porous layer, the movement range of this part of the oil molecules is restricted, thereby restraining the entire oil layer and effectively avoiding the problem of agglomeration or transfer. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic diagram of the metallized film structure of the present invention.

[0020] Reference numerals: 1 insulating dielectric layer; 2 metal layer; 3 protective layer. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0022] A moisture and heat resistant metallized film, comprising an insulating dielectric layer 1, a metal layer 2 and a protective layer 3;

[0023] The protective layer 3 includes a network-shaped nano-carbon porous layer and a modified oil layer, and the modified oil layer includes silicone oil and additives;

[0024] The additives include nano titanium dioxide, modified nano silicon dioxide and polymethyl methacrylate;

[0025] The thickness of the insulating dielectric layer 1 is 3 μm-8 μm, the thickness of the metal layer 2 is 20 nm-40 nm, and the thickness of the protective layer 3 is 10 nm-30 nm.

[0026] The preparation method of the modified nano-silicon dioxide comprises the following steps: the modified nano-silicon dioxide is surface treated with a silane coupling agent to obtain the modified nano-silicon dioxide. Specific embodiments

[0028] Preparation Example 1

[0029] Nano titanium dioxide, modified nano silicon dioxide and polymethyl methacrylate are mixed in a mass ratio of 1:1:1 to prepare an additive.

[0030] Preparation Example 2

[0031] Nano titanium dioxide, modified nano silicon dioxide and polymethyl methacrylate are mixed in a mass ratio of 1.1:0.9:1.4 to prepare an additive.

[0032] Preparation Example 3

[0033] Nano titanium dioxide, modified nano silicon dioxide and polymethyl methacrylate are mixed in a mass ratio of 1.3:0.7:1.8 to prepare an additive.

[0034] Preparation Example 4

[0035] Nano titanium dioxide, modified nano silicon dioxide and polymethyl methacrylate are mixed in a mass ratio of 1.5:0.5:2 to prepare an additive.

[0036] Example 1

[0037] This embodiment provides a method for preparing a moisture-heat resistant metallized film, and the specific steps are as follows:

[0038] S1: Slowly add terephthalic acid into a methanol solvent, stir to dissolve it, and form a terephthalic acid solution with a concentration of 0.01 mol / L. Add zinc nitrate into another portion of methanol solvent, stir to fully dissolve the zinc nitrate, and obtain a 0.05 mol / L transparent zinc ion solution.

[0039] S2: 0.01 g / mL polyethylene glycol is added to the zinc ion solution and mixed evenly to form a mixed solution. The insulating dielectric layer with the metal layer is immersed in the mixed solution. The terephthalic acid solution is slowly added to the mixed solution at a temperature of 25°C and a reaction time of 1 hour. The zinc ions and terephthalic acid molecules will gradually diffuse to the surface of the metal layer to form a continuous MOF layer on the surface of the metal layer.

[0040] S3: The metal film with MOF is transferred to a high-temperature furnace in an inert atmosphere for carbonization treatment to form a network-like nano-carbon porous layer. The heating rate of the high-temperature furnace is 1°C / min, and the carbonization temperature is 500°C.

[0041] S4: Weigh 90 kg of silicone oil and 0.05 kg of additives and mix them evenly to form modified oil. Spray the modified oil onto the network-shaped nanocarbon porous layer in batches until the required thickness of the protective layer is reached. Wait for 15 minutes after each spraying and dry it at 40°C.

[0042] Example 2

[0043] This embodiment provides a method for preparing a moisture-heat resistant metallized film, and the specific steps are as follows:

[0044] S1: slowly add terephthalic acid into a methanol solvent, stir to dissolve it, and form a terephthalic acid solution with a concentration of 0.05 mol / L; add zinc nitrate into another portion of methanol solvent, stir to fully dissolve the zinc nitrate, and obtain a 0.1 mol / L transparent zinc ion solution;

[0045] S2: 0.05 g / mL polyethylene glycol is added to the zinc ion solution and mixed evenly to form a mixed solution. The insulating dielectric layer with the metal layer is immersed in the mixed solution. The terephthalic acid solution is slowly added to the mixed solution at a temperature of 30°C and a reaction time of 2 hours. The zinc ions and terephthalic acid molecules will gradually diffuse to the surface of the metal layer to form a continuous MOF layer on the surface of the metal layer.

[0046] S3: The metal film with MOF is transferred to a high-temperature furnace in an inert atmosphere for carbonization treatment to form a network-like nano-carbon porous layer. The heating rate of the high-temperature furnace is 3°C / min, and the carbonization temperature is 600°C.

[0047] S4: Weigh 95 kg of silicone oil and 0.1 kg of additives and mix them evenly to form modified oil. Spray the modified oil onto the network-shaped nanocarbon porous layer in batches until the required thickness of the protective layer is reached. Wait for 18 minutes after each spraying and dry it at 60°C.

[0048] Example 3

[0049] This embodiment provides a method for preparing a moisture-heat resistant metallized film, and the specific steps are as follows:

[0050] S1: slowly add terephthalic acid into a methanol solvent, stir to dissolve it, and form a 0.1 mol / L terephthalic acid solution; add zinc nitrate into another portion of methanol solvent, stir to fully dissolve the zinc nitrate, and obtain a 0.2 mol / L transparent zinc ion solution;

[0051] S2: 0.1 g / mL polyethylene glycol is added to the zinc ion solution and mixed evenly to form a mixed solution. The insulating dielectric layer with the metal layer is immersed in the mixed solution. The terephthalic acid solution is slowly added to the mixed solution at a temperature of 35°C and a reaction time of 3 hours. The zinc ions and terephthalic acid molecules will gradually diffuse to the surface of the metal layer to form a continuous MOF layer on the surface of the metal layer.

[0052] S3: The metal film with MOF is transferred to a high-temperature furnace in an inert atmosphere for carbonization treatment to form a network-like nano-carbon porous layer. The heating rate of the high-temperature furnace is 5°C / min, and the carbonization temperature is 800°C.

[0053] S4: Weigh 100 kg of silicone oil and 0.2 kg of additives and mix them evenly to form modified oil. Spray the modified oil onto the network-shaped nanocarbon porous layer in batches until the required thickness of the protective layer is reached. Wait for 20 minutes after each spraying and dry it at 80°C.

[0054] Comparative Example 1

[0055] This comparative example is used to prepare a moisture-heat resistant metallized film. The difference from Example 1 is that no additive is added to the modified oil in this comparative example.

[0056] Capacitor moisture and heat resistance test:

[0057] The metallized films prepared in the above Examples 1-3 and Comparative Examples 1-2 are used to prepare capacitors. Example 1 prepares capacitor 1, Example 2 prepares capacitor 2, and so on, until Comparative Example 1 prepares capacitor 4:

[0058] The manufactured capacitors were placed in a 310VAC, 85℃, 85%RH environment for 1500hrs, the capacities before and after treatment were measured, and the capacity change rate was calculated:

[0059] Capacity change rate = (C 1500hr -C 0hr ) / C 0hr ×100%

[0060] In the formula, C 1500hr , C 0hr These are the capacitor capacities before and after wet heat treatment.

[0061] The test results are shown in the following table.

[0062]

[0063] Table 1

[0064] As shown in Table 1, the capacity change rate of the capacitors 1-3 assembled with the metallized film prepared by the present application during the wet heat test for 1500 hours is less than 20%. The network-like nanoporous structure of nanocarbon has a large specific surface area, and a microscopic "anchoring site" is formed on its surface. When the modified oil layer is coated thereon, the silicone oil molecules and the additives therein can be embedded in these sites, so that the network-like nanocarbon porous layer is firmly combined with the silicone oil molecules, so that the oil layer can be evenly dispersed in the initial coating stage to avoid large agglomeration. Since part of the modified oil penetrates into the pores of the network-like nanocarbon porous layer, the movement range of the part of the oil molecules is restricted, thereby restraining the entire oil layer, effectively avoiding the problem of agglomeration or transfer.

[0065] The capacity change rate of capacitor 4 prepared in comparative example 1 is higher than 20% during the 1500 hr damp heat test, because the oil layer formed by the silicone oil molecules is not easy to spread and the metal is partially exposed, resulting in poor damp heat resistance of the metallized film.

[0066] Through further analysis of Table 1, it can be found that the performance of capacitor 2 is better than that of other embodiments. The inventors made the following Examples 4-7 to analyze the influence of the mass ratio of titanium dioxide, modified silicon dioxide and polymethyl methacrylate on the moisture and heat resistance of the capacitor.

[0067] Example 4

[0068] This embodiment is used to prepare a moisture and heat resistant metallized film. The difference from Embodiment 2 is that the additive in this embodiment is prepared using the additive in Embodiment 1.

[0069] Example 5

[0070] This embodiment is used to prepare a moisture and heat resistant metallized film. The difference from Embodiment 2 is that the additive in this embodiment is prepared using the additive in Embodiment 2.

[0071] Example 6

[0072] This embodiment is used to prepare a moisture and heat resistant metallized film. The difference from Embodiment 2 is that the additive in this embodiment is prepared using the additive in Embodiment 3.

[0073] Example 7

[0074] This embodiment is used to prepare a moisture and heat resistant metallized film. The difference from Embodiment 2 is that the additive in this embodiment is prepared using the additive in Embodiment 4.

[0075] The metallized films prepared in the above Examples 4-7 are used to prepare capacitors. Example 4 prepares capacitor 5, and so on until Example 7 prepares capacitor 8:

[0076] The test results are shown in the following table.

[0077]

[0078] Table 2

[0079] It can be seen from Table 2 that the capacity change rate of capacitors 5-8 during the wet heat test for 1500hr is less than 10%. In the process of combining the silicone oil with the network-like nano-carbon porous layer, nano-silicon dioxide, nano-titanium dioxide and polymethyl methacrylate show a synergistic effect. Nano-titanium dioxide is closely connected to the silicone oil molecules through chemical adsorption. The active sites on its surface can capture silicone oil molecules and adjust the molecular distance of silicone oil. During the heating process, this close connection prevents the silicone oil molecules from aggregating due to excessive closeness due to thermal motion, ensuring that the silicone oil is in the nano-carbon porous layer. The modified nano-silica can form a strong chemical bond with the silicone oil on the one hand, and has a certain affinity with the nano-carbon porous layer on the other hand, so it can be partially embedded in the pores of the nano-carbon porous layer, and the nano-carbon porous layer and the silicone oil are "bridged" by chemical bonds to avoid the transfer or agglomeration of the silicone oil due to loosening. The polymethyl methacrylate polymer chain has a certain flexibility. When interacting with the nano-carbon porous layer, its chain segments can be entangled in the nanofibers or pore walls of the nano-carbon porous layer. This entanglement effect provides additional "binding force" for the silicone oil. When the silicone oil tends to flow due to thermal motion or external force, polymethyl methacrylate limits the movement range of the silicone oil and maintains the fixed position of the oil layer on the nanocarbon porous layer by virtue of its entanglement with the nanocarbon porous layer and molecular entanglement with the silicone oil. Titanium dioxide, modified silica and polymethyl methacrylate interact with the nanocarbon porous layer and silicone oil to ensure the stable spreading of silicone oil on the nanocarbon porous layer from multiple dimensions such as physical adsorption, chemical bonding and structural entanglement, effectively overcoming the problems of agglomeration and transfer.

[0080] The above embodiments are only used to illustrate the technical solutions of the present invention, but not to limit them.

Claims

1. A heat-resistant metallized film, characterized in that: including an insulating dielectric layer, a metal layer and a protective layer; The protective layer comprises a network-shaped nano-carbon porous layer and a modified oil layer, wherein the modified oil layer comprises the following components in parts by weight: 90-100 parts of silicone oil and 0.05-0.2 parts of additives.

2. The heat-and-humidity resistant metallized film according to claim 1, characterized in that: The additives include nano titanium dioxide, modified nano silicon dioxide and polymethyl methacrylate, and the mass ratio of the nano titanium dioxide, modified nano silicon dioxide and polymethyl methacrylate is (1-1.5): (0.5-1): (1-2).

3. The heat-and-humidity resistant metallized film according to claim 1, characterized in that: The thickness of the insulating dielectric layer is 3 μm-8 μm, the thickness of the metal layer is 20 nm-40 nm, and the thickness of the protective layer is 10 nm-30 nm.

4. The heat-and-humidity resistant metallized film according to claim 2, characterized in that: The preparation method of the modified nano-silicon dioxide comprises the following steps: the modified nano-silicon dioxide is surface treated with a silane coupling agent to obtain the modified nano-silicon dioxide.

5. A method for preparing a moisture-heat resistant metallized film according to any one of claims 1 to 4, characterized in that: The steps include: S1: slowly adding terephthalic acid into a methanol solvent, stirring to dissolve it, forming a terephthalic acid solution with a concentration of 0.01-0.1 mol / L, adding zinc nitrate into another portion of methanol solvent, stirring to fully dissolve the zinc nitrate, and obtaining a 0.05-0.2 mol / L transparent zinc ion solution; S2: 0.01-0.1 g / mL polyethylene glycol is added to the zinc ion solution and mixed evenly to form a mixed solution. The insulating dielectric layer with the metal layer is immersed in the mixed solution. The terephthalic acid solution is slowly added to the mixed solution. The temperature is 25-35 ° C. The reaction time is 1-3 hours. The zinc ions and terephthalic acid molecules will gradually diffuse to the surface of the metal layer to form a continuous MOF layer on the surface of the metal layer. S3: transferring the metal film grown with MOF to a high-temperature furnace in an inert atmosphere for carbonization treatment to form a network-like nano-carbon porous layer; S4: Evenly mix the silicone oil and the additive according to the ratio to form a modified oil, and spray the modified oil onto the network-shaped nano-carbon porous layer in batches until the required thickness of the protective layer is reached.

6. The method for preparing a moisture-heat resistant metallized film according to claim 5, characterized in that: In step S4, after each spraying, it is necessary to wait for 15-20 minutes and perform drying at a temperature of 40-80°C.

7. The method for preparing a moisture-heat resistant metallized film according to claim 5, characterized in that: In step S3, the heating rate of the high temperature furnace is 1-5°C / min, and the carbonization temperature is 500°C-800°C.

Citation Information

Patent Citations

  • Polypropylene metallized film and processing technology thereof

    CN116083853A

  • Metallized film and film capacitor with same

    CN117777513A

  • Method for producing laminated porous film

    JP2016040354A

  • Metallized film for capacitor and capacitor using the same

    JP2018157055A

  • Metalized film

    WO2019206058A1